The functions of wealth: renters, owners and capitalists across Europe and the United States - Pirmin Fessler; Martin Schürz (Oesterreichische Nationalbank (OeNB), 2018)
Piketty (2017) argues in favor of a multidimensional and relational approach to the analysis of wealth inequality. Specifically, he suggests that social classes should be analyzed in terms of the power and production relations between social groups, not just the percentiles in statistical distributions into which various groups fall. We propose such a relational approach by focusing on different functions of wealth. We operationalize functions of wealth by empirically analyzing the groups of renters, owners, and capitalists. Employing recent European and US data, we find that classifying households based on these decisive functions of wealth aligns well with the wealth distribution, in ways that vary considerably across countries. We discuss many potential advantages of this class typology in measuring and analyzing wealth and wealth inequality in particular.
Keywords: D14; D15; D31; D63; Z13; 330; wealth; inequality; households; survey data; class; economic strati cation